A study on the clinical spectrum and electrocardiographic changes in scorpion sting envenomation - Senthilkumar, M. J.; Kumar, P. Suresh; Nagalingam, Saranya (International Journal of Research in Medical Sciences, 2019)
Background: Scorpion stings, though not a big problem in many developed countries, it is a major public health problem in underdeveloped and in some developing countries all over the world. Objectives was to study on the clinical spectrum and electrocardiographic changes in scorpion sting envenomation. Methods: This study was conducted in a tertiary care institute after obtaining the IEC clearance and informed consent from the patients for a period of 6 months from January 2018 to June 2018. All the patients admitted to the toxicology ward and general ward with scorpion envenomation during the study period were included in the study. A total number of 53 cases of scorpion envenomation and 20 healthy patients from the outpatient department of General medicine, were taken as controls. Results: Fifty-nine percent of the patients presented with Grade 1 envenomation, seven percent with Grade 2 and thirty four percent with Grade 3 envenomation. Local pain (83%) and tachycardia (19%) were the commonest presenting symptom and sign respectively. Sinus tachycardia (6%) was the commonest ECG abnormality seen in the study. There was statistical significance in the relationship between ECG change and biochemical marker CK-MB. Conclusions: Scorpion envenomation in adults needs to be studied to identify the high-risk groups and to assess the morbidity caused it. There was no mortality due to scorpion sting in the study period and significant correlation between the time delay and severity of envenomation was found which indicates a need for immediate medical care following scorpion sting.